Benefits, barriers and opinions on multidisciplinary team meetings: a survey in Swedish cancer care - Linn Rosell; Nathalie Alexandersson; Oskar Hagberg; Mef Nilbert (BMC, 2018)
Abstract Background Case review and discussion at multidisciplinary team meetings (MDTMs) have evolved into standard practice in cancer care with the aim to provide evidence-based treatment recommendations. As a basis for work to optimize the MDTMs, we investigated participants' views on the meeting function, including perceived benefits and barriers. Methods In a cross-sectional study design, 244 health professionals from south Sweden rated MDTM meeting structure and function, benefits from these meetings and barriers to reach a treatment recommendation. Results The top-ranked advantages from MDTMs were support for patient management and competence development. Low ratings applied to monitoring patients for clinical trial inclusion and structured work to improve the MDTM. Nurses and cancer care coordinators did less often than physicians report involvement in the case discussions. Major benefits from MDTM were reported to be more accurate treatment recommendations, multidisciplinary evaluation and adherence to clinical guidelines. Major barriers to a joint treatment recommendation were reported to be need for supplementary investigations and insufficient pathology reports. Conclusions Health professionals' report multiple benefits from MDTMs, but also define areas for improvement, e.g. access to complete information and clarified roles for the different health professions. The emerging picture suggests that structures for regular MDTM evaluations and increased focus on patient-related perspectives should be developed and implemented.